A Multimethod Analysis of Incompleteness and Visual "Not Just Right" Experiences in Body Dysmorphic Disorder. Issue 5 (September 2020) - Summers, Berta J.; Wilver, Natalie L.; Garratt, Grace H.; Cougle, Jesse R.
Abstract: Individuals with body dysmorphic disorder (BDD) often report engaging in repetitive behaviors aimed at reducing feelings of imperfection anchored to their appearance. "Not just right" experiences (NJREs) and incompleteness (INC) are constructs related to perfectionism that have traditionally been studied in obsessive-compulsive disorder, though recent research has also linked these phenomena to BDD. We sought to replicate and extend this research via two studies. Study 1 examined BDD symptoms, INC, as well as harm avoidance (HA) in an unselected sample ( N = 179); moderate associations were observed between symptoms and both INC and HA. Participants also completed a novel visual NJRE task in which they were shown appearance-related and non-appearance-related images meant to evoke an NJRE response (i.e., discomfort and urge to "fix" stimuli). BDD symptoms predicted reactivity to appearance-related NJRE stimuli above negative affect. Study 2 compared INC, HA, and task reactivity in a BDD sample ( N = 50) to nonpsychiatric controls ( N = 44). The BDD group evidenced greater INC, HA, and reactivity to both appearance and nonappearance NJRE stimuli, relative to controls; however, group differences did not remain after controlling for age and negative affect. These studies broadly corroborate previous research highlighting NJREs and INC as potential vulnerability factors relevant to BDD, though these phenomena may not be specific to BDD symptoms. Highlights: We tested the specificity of incompleteness and in vivo NJREs to BDD via 2 studies Both INC and harm avoidance demonstrated moderate associations with BDD symptoms Symptoms predicted reactivity to appearance NJRE stimuli above negative affect A BDD group showed greater INC, HA, and in vivo reactivity, relative to controls The study contributes a novel visual NJRE task tapping appearance-related stimuli